2015
DOI: 10.1186/s12888-015-0595-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the level of institutionalisation found in psychiatric housing services associated with the severity of illness and the functional impairment of the patients? A patient record analysis

Abstract: BackgroundIn this cross-sectional study, we investigated whether clinical, social, financial, and care variables were associated with different accommodation settings for individuals suffering from severe and persistent mental disorders.MethodElectronic record data of 250 patients who fulfilled the criteria for persistent and severe mental illness were used. Multiple linear regression models were applied to analyse associations between the types and the costs of housing services and the patients’ severity of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, a limitation may be that the data used in this study were gathered in the context of another study [32]; therefore, the recruitment of participating organisations and service users was not totally random. When we compare these characteristics with (inter)national studies on service users of housing services, though, we can conclude that the participants of this study are representative for this target group [13, 19]. The use of validated client-rated measures is another strength.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a limitation may be that the data used in this study were gathered in the context of another study [32]; therefore, the recruitment of participating organisations and service users was not totally random. When we compare these characteristics with (inter)national studies on service users of housing services, though, we can conclude that the participants of this study are representative for this target group [13, 19]. The use of validated client-rated measures is another strength.…”
Section: Discussionmentioning
confidence: 95%
“…For example, service users who live in staffed sheltered facilities have comparable levels of functioning and problem severity compared to service users receiving outpatient housing support [17, 19]. This raises the questions of to what extent housing services provide the appropriate support to their users and to what extent the recovery needs of these service users are met.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that staff attitudes towards recovery influence people with SMI’s level of participation, inhibiting their recovery ( Bitter et al, 2017 ; Linhorst et al, 2005 ; Macpherson et al, 2004 ; Pandiani et al, 1994 ) and likelihood of moving on to more independent living ( Killaspy et al, 2013 ; Killaspy et al, 2019 ). Other personal and environmental factors can affect an individual’s experience of personal empowerment including their illness experience, restrictions imposed by compulsory treatment orders and rules within SA which can restrict choices and involvement in decision making ( Brolin et al, 2018 ; Fossey et al, 2006 ; Nelson et al, 2001 ; Sandhu et al, 2017 ; Valdes-Stauber & Kilian, 2015 ). These environmental factors mean that staff have to uphold rules while also supporting individuals, limiting flexibility of approach which can hinder effective support for recovery ( Bengtsson-Tops et al, 2014 ; Coffey et al, 2019 ; Nelson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…MHCPs' lack of resources and flexibility regarding time and content), and contextual circumstances (especially , 2012;Dehn et al, 2022;Martinelli et al, 2019;Nordentoft et al, 2012). However, there is some evidence that questions a clear association between disease severity and the degree of institutionalisation (de Heer-Wunderink et al, 2012;Valdes-Stauber & Kilian, 2015). Thus, it remains a question of further research if service users in RCFs have actually more severe impairments, or if the view of service users' non-readiness for independent living reflects the traditional continuum approach, which aims to first train and prepare service users before considering them competent to live independently.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clinical equivalence of institutionalised and outreach housing rehabilitation, many mental healthcare professionals (MHCPs) assumed different levels of support and supervision. However, neither these perceptions nor the degree of institutionalisation in the respective housing rehabilitation setting seem to reflect the severity of the service users' illness and functional impairment (Valdes-Stauber & Kilian, 2015).…”
Section: Introductionmentioning
confidence: 98%